2022
DOI: 10.3390/molecules27092831
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols: Extraction, Identification, Bioavailability, and Role for Prevention and Treatment of Colorectal and Prostate Cancers

Abstract: Fruits, vegetables, and other edible plants in our diet have numerous health benefits, due to the bioactive compounds in these food items, including polyphenols. These plants are a rich and promising source of natural products and phytochemicals that can be used to treat and prevent numerous diseases and prevent the progression of cancer. Dietary polyphenols exhibit chemo-preventive and therapeutic effects against various ailments, including several types of cancer. The current study focuses on polyphenol’s tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…Plant polyphenols can be considered as safer anti-carcinogenic macromolecules because of their cytoprotective activities in normal cells and their simultaneous cytotoxic response toward malignant cells [ 54 ]. T. terrestris methanol extract in the previous section linked with inhibition of carcinogens such as superoxide, hydrogen peroxide, and hydroxyl radicals possessed anti-cancer activity against breast cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Plant polyphenols can be considered as safer anti-carcinogenic macromolecules because of their cytoprotective activities in normal cells and their simultaneous cytotoxic response toward malignant cells [ 54 ]. T. terrestris methanol extract in the previous section linked with inhibition of carcinogens such as superoxide, hydrogen peroxide, and hydroxyl radicals possessed anti-cancer activity against breast cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of greater amounts of fruits and berries, especially citrus fruits, in the human diet is suggested to help in cancer prevention and to suppress cancer growth [ 5 , 6 , 7 ]. The main active compounds of fruits are the polyphenolic compound flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…It can be stated that high antioxidant activity could be attained by adding the bioactive compounds quantified in this study. A plethora of literature showed a positive relationship between specific bioactive compounds and antioxidant activity [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In an earlier study, the antioxidant activity of OB-EO was reported as IC 50 6.68 mg/mL and 62.2 mg ascorbic acid equivalent (AAE)/g in DPPH and FRAP assay, respectively, and was ascribed to the presence of α-pinene, γ-terpinene, 1,8-cineole, limonene, linalool, and linalyl acetate [ 45 ], supporting the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%